The Effectiveness of Dual Antiplatelet Treatment in Acute Ischemic Stroke Patients with Intracranial Arterial Stenosis: A Subgroup Analysis of CLAIR Study. Issue 8 (December 2013) - Wang, Xin; Lin, Wen Hua; Zhao, Yu Dong; Chen, Xiang Yan; Leung, Thomas W.; Chen, Christopher; Fu, Jianhui; Markus, Hugh; Hao, Qing; Wong, Ka Sing; ,
Background: Dual antiplatelet therapy with clopidogrel and aspirin reduces the presence and number of microembolic signals in patients with large artery disease. However, whether it is effective in patients with intracranial disease alone remains uncertain. We performed a subgroup analysis of the The CLopidogrel plus Aspirin for Infarction Reduction (CLAIR in acute stroke or transient ischemic attack patients with large artery stenosis and microembolic signals) study of only patients with intracranial occlusive disease, excluding those with extra cranial disease. Methods: CLAIR was a randomized-controlled, open-label, multicenter clinical trial with blinded outcome evaluation, which recruited patients with symptoms of ischemic stroke or transient ischemic attack within seven-days of onset, with large artery stenosis verified by transcranial Doppler and carotid ultrasound, and with microembolic signals detected by transcranial Doppler recording. All patients were randomized to receive clopidogrel plus aspirin daily for seven-days (dual treatment), or aspirin alone for seven-days (monotherapy). Repeated transcranial Doppler recordings for microembolic signals were made on day one, two, and seven. This subgroup study only analyzed the patients with purely intracranial large artery disease and excluded those with extra cranial stenosis. Results: There were 70 patients recruited with purely intracranial stenosis, 34 in the dual treatment group and 36 in the monotherapy group. The proportion of the patients with positive emboli at day seven in the dual treatment group was significantly lower than that in the monotherapy group (relative risk reduction 56·5%, 95% confidence interval 2·5–80·6; P = 0·029). The number of emboli in the dual treatment group decreased significantly at day two ( P = 0·043) and day seven ( P = 0·018) compared with the monotherapy group. After adjustment for the number of emboli at day one, the effect of dual treatment was still significant for the reduction of presence (relative risk reduction 56·0%; 95% confidence interval 5·4–79·6; P = 0·036) and number (adjusted mean difference −0·9; 95% confidence interval −1·5 to −0·3; P = 0·004) of positive emboli at day seven. Conclusions: Dual treatment with clopidogrel and aspirin for seven-days is more effective than aspirin alone to reduce microembolic signals in patients with intracranial arterial stenosis.